2015
DOI: 10.3389/fphys.2015.00381
|View full text |Cite|
|
Sign up to set email alerts
|

Immunosuppressant MPA Modulates Tight Junction through Epigenetic Activation of MLCK/MLC-2 Pathway via p38MAPK

Abstract: Background: Mycophenolic acid (MPA) is an important immunosuppressive drug (ISD) prescribed to prevent graft rejection in the organ transplanted patients, however, its use is also associated with adverse side effects like sporadic gastrointestinal (GI) disturbances. Recently, we reported the MPA induced tight junctions (TJs) deregulation which involves MLCK/MLC-2 pathway. Here, we investigated the global histone acetylation as well as gene-specific chromatin signature of several genes associated with TJs regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Two follow up studies showed that the disruption of intestinal tight junctions was associated with chromatin histone modifications, including an increase in midkine concentrations2829. In contrast to these targeted studies, as aforementioned, in the present study, we took a comprehensive, non-targeted, unique combined proteo-metabolomic approach that resulted in a much more complete picture of the time- and dose-dependent effects of mycophenolic acid on intestinal cell protein concentrations and cell metabolism at various levels of guanosine supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Two follow up studies showed that the disruption of intestinal tight junctions was associated with chromatin histone modifications, including an increase in midkine concentrations2829. In contrast to these targeted studies, as aforementioned, in the present study, we took a comprehensive, non-targeted, unique combined proteo-metabolomic approach that resulted in a much more complete picture of the time- and dose-dependent effects of mycophenolic acid on intestinal cell protein concentrations and cell metabolism at various levels of guanosine supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…TEER was considered as an indicator of the intact TJ. We used a Millicell-ERS voltohmmeter (Millipore, Bedford, MA) to detect the value of TEER group according to previously reported (23). The monolayer wells with TEER Ͼ400 ⍀·cm 2 were chosen to treat with or without TNF-␣ (10 ng/ml) in the basolateral side of the Transwell chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it makes sense to inhibit IL-8 expression to relieve the acute onset of IBD and prevent the advancement of the inflammation-associated colonic carcinoma. It is acknowledged that IL-8 transcription is regulated by the JNK/c-Jun/AP-1 pathway(23,33). TNF-␣ results in a high level of active phosphorylated c-Jun NH 2terminal kinase (p-JNK), which could phosphorylate c-Jun.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The biological effects on activation on these inflammatory cytokines lead to the recruitment and activation of kinases favoring the phosphorylation-dependent disruption of TJ proteins (Figure 3 ). Other major mediators of H. pylori- induced pathogenesis include Protein kinase C (PKC) (Tohidpour, 2016 ), mitogen-activated protein kinase (MAPK) (Ding et al, 2008 ), p38, extracellular signal-regulated kinases (ERK) (Seo et al, 2013 ), and myosin light chain (MLC) (Khan et al, 2015 ). Interplay of these modulators has been shown in the designed model and thus their overall inhibitory effect on TJ proteins has been revealed.…”
Section: Methodsmentioning
confidence: 99%